Herpesviruses Serology Distinguishes Different Subgroups of Patients From the United Kingdom Myalgic Encephalomyelitis/Chronic Fatigue Syndrome Biobank - Domingues, Tiago Dias; Grabowska, Anna D.; Lee, Ji-Sook; Ameijeiras-Alonso, Jose; Westermeier, Francisco; Scheibenbogen, Carmen; Cliff, Jacqueline M.; Nacul, Luis; Lacerda, Eliana M.; Mouriño, Helena; Sepúlveda, Nuno (Frontiers in Medicine, 2021)
The evidence of an association between Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) and chronic herpesviruses infections remains inconclusive. Two possible reasons for this lack of consistent evidence are the large heterogeneity of the patients’ population with different disease triggers and the use of arbitrary cutoffs for defining seropositivity. In this work we re-analyzed previously published serological data related to 7 herpesvirus antigens. These data were collected as part of the United Kingdom ME/CFS Biobank (UKMEB). In our re-analysis, patients with ME/CFS were subdivided into four major subgroups related to the disease triggers: S0 - 42 patients who did not know their disease trigger; S1 - 43 patients who reported a non-infection trigger; S2 - 93 patients who reported an infection trigger, but that infection was not confirmed by a lab test; and S3 - 48 patients who reported an infection trigger and that infection was confirmed by a lab test. In accordance with a sensitivity analysis, the data were compared to those from 99 healthy controls allowing the seropositivity cutoffs to vary within a wide range of possible values. We found a negative association between S1 and seropositivity to Epstein-Barr virus (VCA and EBNA1 antigens) and Varicella-Zoster virus. However, the significance of this finding was affected by the seropositivity cutoff used. We also found that S3 had a lower seroprevalence to the human cytomegalovirus when compared to healthy controls for all cutoffs used for seropositivity. In summary, herpesviruses serology could distinguish subgroups of ME/CFS patients according to their disease trigger.